The Principal’s Role in Improving Teacher’s Professionalism - Sumarni, Sumarni; Widiyatsih, Tri; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2023)
In this study, the principal’s role in raising the professionalism of SD Negeri 34 Prabumulih teachers will be identified and analyzed, as well as the principal’s actions in doing so. Additionally, the supporting factors used by the principal to raise teacher’s professionalism at SDN 34 Prabumulih will be examined. To gain a comprehensive understanding of the role played by the school principal in raising teacher’s professionalism at SD Negeri 34 Prabumulih, a qualitative descriptive research methodology was adopted. Observable behavior, written or spoken statements from people, and descriptive data approaches are used in analysis. The results showed that school principals work as educators, managers, administrators, supervisors, and motivators in an effort to increase teacher professional competency. The SDN 34 Prabumulih principal also fulfills his responsibilities as manager and administrator by putting up a variety of programs, from short-term to long-term programs, and managing a variety of school administrations. Along with that, the director of SDN 34, Prabumulih, also continuously assesses instructors’ performance in learning activities while also remembering to encourage and motivate them to do better.